2004
DOI: 10.1002/jsfa.1703
|View full text |Cite
|
Sign up to set email alerts
|

Effect of foliar sprays containing calcium, magnesium and titanium on peach (Prunus persica L) fruit quality

Abstract: Sprays containing Ca 2+ , Mg 2+ or Ti 4+ were applied to peach trees in several combinations. Effects of treatments on the commercial quality of fruits, especially focused on improving their mechanical properties, are discussed. All treatments containing titanium increased tree performance (branch elongation, flowering and fruit set intensities) and fruit size. At harvest, fruits from Ti-treated trees showed improved resistance to compression and penetration, as well as a decrease in weight loss during posthar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…nucipersica ) improved fruit color, ripening index and firmness at harvest (Serrano et al, 2004). Peach fruit weight and firmness significantly increased, and weight loss during storage significantly decreased after foliar application of Ti, or Ti with Ca and/or Mg before harvest (Alcaraz-Lopez et al, 2004a,b). …”
Section: Ti Improves Plant Performancementioning
confidence: 99%
See 1 more Smart Citation
“…nucipersica ) improved fruit color, ripening index and firmness at harvest (Serrano et al, 2004). Peach fruit weight and firmness significantly increased, and weight loss during storage significantly decreased after foliar application of Ti, or Ti with Ca and/or Mg before harvest (Alcaraz-Lopez et al, 2004a,b). …”
Section: Ti Improves Plant Performancementioning
confidence: 99%
“…Carvajal and Alcaraz (1995) demonstrated that foliar application of Ti-ascorbate resulted in an increase of Fe concentrations in leaves, fruits, chloroplasts, and chromoplasts of red pepper plants. Foliar application of Ti resulted in 39% and 35.7% increase of Fe in peel and flesh of peach fruit (Alcaraz-Lopez et al, 2004a,b). Leaves of paprika pepper sprayed with Ti-ascorbate increased Fe uptake by 50% in a greenhouse experiment and close to 100% in a field experiment, and leaf peroxidase and catalase activities also significantly increased due to the Ti-ascorbate application (Carvajal et al, 1995).…”
Section: Contributions To Fe Homeostasismentioning
confidence: 99%
“…Fruits therefore commonly have low Ca concentrations and show high susceptibility to Ca deficiency problems. The use of preharvest Ca sprays on apple (Hickey et al, 1995;Fallahi et al, 1997), plum (Alcaraz-López et al, 2003, 2004a, peach (Alcaraz-López et al, 2004b) and nectarine (AlcarazLópez et al, 2004c) do not increase total or cell wall Ca concentrations sufficiently to affect fruit firmness. However, it has been reported that when Ca is applied in combination with polypeptidic N, and especially with leaf assimilatable Ti +4 ascorbate, fruits show a significant increase in skin and flesh Ca, are firmer, and have a longer storage life (Alcaraz-López et al, 2003, 2004a.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium has been successfully used to extend storage life by retarding fruit ripening 1–3. Since little calcium translocation from leaves to the fruits occurs during fruit growth, direct calcium applications on the fruit surface is recommended and calcium sprays have been reported to be particularly effective in increasing calcium levels in many fleshy fruits,4–8 including peach and nectarine fruits 9, 10. Even in calcareous soils, pre‐harvest calcium sprays have been proved beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium sprays are exploited as a main tool in integrated peach production leading to environmentally more friendly growing techniques, promptly by increasing tissue firmness9–11 and resistance to brown rot 11, 12. The beneficial effects of pre‐harvest calcium sprays depend on many parameters, including salt type and supply period,11 as well as growth conditions and cultivar,10 and contradictory results regarding their effect in peach fruits have been reported 10, 13.…”
Section: Introductionmentioning
confidence: 99%